Seismic performance of cantilever retaining wall under different earthquake loading - Muhammad Hasnun Hasib, Mohd Ariffin (2019)
During past recent years, the number of building structural damage affected by earthquake is increase in Malaysia especially in Sabah. The study was conducted because the tremors in Malaysia were due to the seismic wave generated from the earthquake that occurred in neighbouring countries or low scale earthquake that occured. The reason of failure the structure because of inadequate design by Engineer without considering seismic effect in while designing the structure. Hence, engineers need concerned in lack of consideration of seismic design in Malaysia Standard procedure which can be seen from the seismic performance and vulnerability of cantilever retaining wall that widely used in Malaysia. Retaining wall structures mostly used in retaining the lateral earth pressure that is critical and important to prevent soil from collapse and erode which also held the soil that give the strength to the building and this structure may occur damage and movement due to seismic effect. Therefore, this paper objective is to study the behaviour and dynamic characteristics of retaining wall and asses the resistance capacity of the structure under different earthquake loading. Hence, the cantilever retaining wall simulated by modelled and analysed using finite element seismic response by SAP2000 software under different type of analysis. The analysis that covered in this research is free vibration analysis, time history analysis and response spectrum analysis under two different earthquakes loading. The earthquake loading is obtained from Malaysia Meteorological Department which is Acheh and Elcentro earthquake that implemented in the analysis to do the comparison in dynamic characteristic of cantilever retaining wall. It can summarize that, the retaining wall structures generally capable of resisting low and major seismicity and also can yield potential different earthquake loading.